Symmetric Training Sequence-Based Carrier Frequency Offset Estimation Scheme for Coherent Free-Space Optical Communication - Xinyu Tang; Liqian Wang; Shanyong Cai; Qin Mei; Zhiguo Zhang (IEEE Photonics Journal, 2022)
In this paper, a symmetric training sequence-based (STSB) carrier frequency offset estimation (FOE) scheme for coherent free-space optical (CFSO) communication is proposed. In the proposed technique, we exploit the training-sequence-based (TSB) carrier FOE algorithm to the CFSO communication system in the quadrature phase-shift keying (QPSK) modulation format. A symmetric training sequence, tailored to the carrier FOE algorithm for atmospheric turbulence channel, is formulated to accurately identify the correct temporal position of a data frame from received signals. Unlike the 4th power algorithm, the proposed algorithm requires only the identified training sequence and the symmetric sequence of the original training sequence in the FOE stage, performing a single multiplication to accurately remove the signal modulation phase. In this way, the proposed technique significantly improves the estimation accuracy. Furthermore, by avoiding the time-consuming 4th power operation, the proposed method reduces the computational complexity while expanding the FOE range. Therefore, when compared with existing algorithms, our proposed technique can achieve more accurate timing, a wider estimation range, and lower complexity. A 10-Gbps QPSK CFSO communication transmission experiment with different turbulence channels was carried out to validate the proposed technique and the improvement in receiver sensitivity.